Keep talented Employees onboard by Work Engagement: Dark behaviors (Blame Attributions, bullying and Turnover Intention) in Organization - Jamshaid, Samrah; Malik, Dr. Najma I; Atta, Dr. Mohsin; Haider, Adnan Ali; Jamshad, Saba; Jamshed, Kamran (The journal of contemporary issues in business and government, 2021)
Every organization has a dark side indeed and the present study aimed to explore dark side behaviors in higher education institutes from the perspective of blame attribution, workplace bullying, and turnover intention which needed to be recognized. These behaviors considered being deviant behavior affects teachers both emotionally and physically. Current study aimed to explore the concept of keeping intact the talented teacher through work engagement while battling with dark behaviors. Study further analyzed the mediating role of work engagement in the relationship between workplace bullying and turnover intention among teachers of HEIs. Quantitative research with the use of survey design and self-administered questionnaire was conducted among upon a sample of purposively selected teachers from Higher Education Institutes (HEIs) in Sargodha, Pakistan, was carried out during March to July 2019. Utrecht Work Engagement Scale (Schaufeli, et al., 2002), Blame attribution scale (Gudjonsson & Singh, 1989), Negative Act Questionnaire (Einarsen, Raknes & Helleosy, 1994), and Turnover Intention scale (Mitchell, et al., 2001) were used to measure the constructs of study. Regression analysis reveals work engagement was a significant predictor for blame attribution, workplace bullying, and turnover intention. Findings also revealed that work engagement was a key booster to keep talented employees on board while tackling workplace bullying and turnover intention. Findings of the study were helpful for organizations to keep their talented employees on board and for employees to cope with dark behaviors.